Caveolin-1-deficient fibroblasts promote migration, invasion, and stemness via activating the TGF-β/Smad signaling pathway in breast cancer cells - Huang, Qingyun; Wu, Longyuan; Wang, Yi; Kong, Xinyu; Xiao, Xinhua; Huang, Qiyuan; Li, Miao; Zhai, Yujia; Shi, Fuxiu; Zhao, Ruichen; Zhong, Junpei; Xiong, Lixia (Acta biochimica et biophysica Sinica, 2022)
Cancer-associated fibroblasts (CAFs) represent one of the main components in the tumor stroma and play a key role in breast cancer progression. Transforming growth factor-β (TGF-β) has been established to mediate breast cancer metastasis by regulating the epithelial-mesenchymal transition (EMT) and stemness of cancer cells. Caveolin-1 (CAV-1) is a scaffold protein of caveolae that is related to the proliferation and metabolism of cancer cells. It is now well demonstrated that CAV-1 deficiency in the tumor stroma is positively correlated with distant metastasis, but the mechanism remains unclear. Here, we explore whether CAV-1-deficient fibroblasts play an essential role in the EMT and stemness of breast cancer cells (BCCs) through TGF-β signaling. We establish a specific small interfering RNA (siRNA) to inhibit CAV-1 expression in fibroblasts and coculture them with BCCs to investigate the effect of CAV‑1-deficient fibroblasts and the tumor microenvironment on breast cancer progression. This study refreshingly points out that CAV-1 deficiency in fibroblasts enhances TGF-β1 secretion and then activates the TGF-β1/Smad signaling pathway of BCCs, thus promoting the metastasis and stemness of BCCs. Collectively, our findings indicate an unexpected role of CAV-1 deficiency in fibroblasts and the tumor microenvironment as a permissive factor, which is regulated by the TGF-β1 signaling pathway in BCCs.